Exploring maths 5 : teacher's book - Fisher, Tony; Hyde, Rosalyn; Jennings, Sue; Longstaffe, Jonathan (Great Britain, Scotprint : Pearson Longman, 2008)
its about the powers and roots, functions and graph, equations and formula, 2D and 3D shapes
Includes index and bibliographies
Keywords: Fractions -- mathematics; Probabilities -- mathematics; Measurements -- mathematics; Equations -- mathematics